Peningkatan Kompetensi Konten Kreatif Penyuluh Agama Melalui Pemanfaatan Aplikasi Mobile di Era Digital - Lakry, Lakry Maltaf Putra; Amuharnis; Arief Rahmadian Aswin; Arman; Nurhidayat; Sirait, Weri (Faatuatua Media Karya, 2025)
Globalization and technological advancements have driven religious counselors to adapt in delivering relevant religious messages. However, the limited use of digital technology, particularly mobile applications, poses a significant challenge, especially among religious counselors. This training aims to enhance the competence and directly motivate religious counselors to create creative religious content using mobile devices. The training involves more than 40 district religious counselors from various digital skill backgrounds. Adopting a participatory approach, the training includes preparation and needs identification, mobile app training, content creation and testing, evaluation and reflection, as well as ongoing mentoring. The results of this training show a significant improvement in participants' digital skills; 70% of participants, who initially struggled with graphic design apps, now achieve 85% capability, and video editing has increased from 30% to 80%. Participants successfully created and published various visual religious content such as short videos, images, and infographics using apps like Capcut, Canva, KineMaster, InShot, Filmora, ShotCut, Vidma, and YouCut. These visual contents proved more effective in attracting audiences, with an average of 30-40% more interaction compared to text-based content. Nonetheless, challenges related to device limitations and technical difficulties still need to be addressed through continuous mentoring and better access to technology. Overall, this training successfully bridges the digital divide and emphasizes the great potential of technology in supporting innovative and effective religious outreach in the digital era.